2022
DOI: 10.1093/tbm/ibac001
|View full text |Cite|
|
Sign up to set email alerts
|

Feedback on Instagram posts for a gestational weight gain intervention

Abstract: Lay Summary Lifestyle interventions can facilitate healthy gestational weight gain but attending in-person meetings can be challenging. The majority of young women use Instagram and pregnancy is a popular topic, suggesting that Instagram might be a means to deliver a pregnancy weight gain intervention. In this study, we asked pregnant women with pre-pregnancy overweight or obesity to join a private group on Instagram and provide feedback on intervention posts about healthy eating and physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Additionally, some participants expressed concern that other women would make negative judgments about their bodies, weight gain, food choices, or exercise habits. This finding echoes concerns about being shamed and stigmatized shared by women with pre-pregnancy obesity in previous studies ( 15 , 31 ). Women also referenced the possibility of feeling bad about themselves after comparing themselves to other women in the group, which aligns with the results of a survey of pregnant women in the UK which found that half compared their pregnancy to others on Facebook, and the more women compared themselves on Facebook, the more negative they felt about their body ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, some participants expressed concern that other women would make negative judgments about their bodies, weight gain, food choices, or exercise habits. This finding echoes concerns about being shamed and stigmatized shared by women with pre-pregnancy obesity in previous studies ( 15 , 31 ). Women also referenced the possibility of feeling bad about themselves after comparing themselves to other women in the group, which aligns with the results of a survey of pregnant women in the UK which found that half compared their pregnancy to others on Facebook, and the more women compared themselves on Facebook, the more negative they felt about their body ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
“…Together, our results suggest a focus on fostering a positive, supportive group culture may be key to engaging women in Instagram-delivered lifestyle interventions. In a previous study, pregnant women suggested that setting clear expectations that photos don’t have to be “Instagram worthy” and having the interventionist model sharing unedited photos of their own imperfect life as ways to create a supportive group culture and promote engagement in an Instagram-delivered GWG intervention ( 15 ). Social media-delivered intervention components focused on body positivity and self-compassion have been perceived positively by pregnant women ( 34 ) and new mothers ( 35 ), and may buffer against the potential for developing unhealthy behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,41,48 Six studies also employed questionnaires and surveys to obtain additional data. 37,38,49,57,60,62 All studies included in the review had high CASP scores, with two scores of 17 and the remainder between 18-20 out of a maximum score of 20.…”
Section: Resultsmentioning
confidence: 99%
“…Many people turn to Instagram for information and support during their pregnancies (63), and as of late November 2022, 24.6 million and 20.7 million Instagram posts included the hashtags #pregnant or #pregnancy, respectively. In our previous work, we found that creating a private group on Instagram was feasible and acceptable to pregnant women, including switching to a second account to view intervention content, and that the majority of women in the study would be interested in receiving a lifestyle intervention on this platform (64) Open Access Statement: This is an Open Access article distributed in accordance with the Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International License (CC BY-NC-ND 4.0), which permits the noncommercial replication and distribution of the article with the strict proviso that no changes or edits are made and the original work is properly cited (including links to both the formal publication through the relevant DOI and the license). See: https://creativecommons.org/licenses/by-nc-nd/4.0/.…”
Section: Discussionmentioning
confidence: 99%